2017
DOI: 10.17221/136/2016-pps
|View full text |Cite
|
Sign up to set email alerts
|

Field efficacy of brief exposure of adults of six storage pests to nitrogen-controlled atmospheres

Abstract: Aulicky R., Kolar V., Plachy J., Stejskal V. (2017): Field efficacy of brief exposure of adults of six storage pests to nitrogen-controlled atmospheres. Plant Protect. Sci., 53: 169-176.The efficacy of a brief exposure (1, 7, and 10 days) to a nitrogen-controlled atmosphere (N-CA) for major storage pests in a field validation study in the Czech Republic is reported. The main goal was to estimate how quickly the mobile adult stages of six species of storage beetles (oryzaephilus surinamensis, cryptolestes ferru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…In our case, this is where we have found most of the survival, suggesting that the exposure intervals should be longer. Vials with already-infested grains have been proven useful in different types of trials at a commercial scale, such as in heat treatments [ 32 ], phosphine application [ 33 , 34 , 35 ], and also in modified atmospheres [ 15 , 17 , 19 ]. This technique suggested that, in contrast with T. confusum , our tests showed that the “short protocol” was unable to provide 100% kill of R. dominica adults.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, this is where we have found most of the survival, suggesting that the exposure intervals should be longer. Vials with already-infested grains have been proven useful in different types of trials at a commercial scale, such as in heat treatments [ 32 ], phosphine application [ 33 , 34 , 35 ], and also in modified atmospheres [ 15 , 17 , 19 ]. This technique suggested that, in contrast with T. confusum , our tests showed that the “short protocol” was unable to provide 100% kill of R. dominica adults.…”
Section: Discussionmentioning
confidence: 99%
“…The stock cultures were set up by introducing newly emerged beetles (about three hundred adults) in two-kg capacity jars, half filled with previously sterilized and conditioned standard diet. The insect standard diet was composed of wheat flour, crushed wheat and dry yeast powder at 5:5:1, respectively according to the method described by Leelaja et al (2007) and Kolar et al (2017). The jars were tightly covered with muslin cloth, held in place by rubber bands and the adults were left to oviposit for two weeks, then removed by sieving.…”
Section: Insect Rearingmentioning
confidence: 99%
“…Moreover, this application exceeded three weeks, which indicates the increased duration that is needed in large structures [25]. However, follow-up trials in silos in the Czech Republic provided complete (100%) mortality of O. surinamensis, T. confusum, T. castaneum, S. oryzae, the rusty grain beetle, Cryptolestes ferrugineus (Stephens) (Coleoptera: Laemophloeidae), and the granary weevil, Sitophilus granarius (L.) (Coleoptera: Curculionidae), but again in increased exposure intervals [26].…”
Section: Application Of Nitrogen In Chambers and Silosmentioning
confidence: 99%